AHP 40: Review: MAPPING SHANGRILA - Katia, Buffetrille (Asian Highlands Perspectives, 2018)
Emily Yeh and Chris Coggins have gathered a collection of ten articles published under what appears as a very contradictory title: Mapping Shangrila. Contested Landscapes in the Sino-Tibetan Borderlands. Since Peter Bishop's The Myth of Shangri la (1989) and Donald Lopez's Prisoners of Shangri la (1998), several books have appeared on Tibet and its relation with the mythical realm created by James Hilton (1900-1954). Meanwhile, Tibetans and Chinese officials in Yunnan have succeeded in establishing Hilton's imaginary place on earth in a real place, populated by real people. In 2002, the city of Gyalthang (Rgyal thang; Ch, Zhongdian), was renamed Shangrila, or Xiangelila as it is rendered in Chinese language. The Shangrila of this book covers a geographic area much larger than Rgyal thang and its surroundings, however. It deals with what the editors qualify as the "Sino-Tibetan Borderlands": places in Kham and Amdo that are undertaking a similar process of "Shangrilazation." ..